Odpowiedzi

2010-02-24T17:11:16+01:00
A) (3x-2y) + (-4x-y)=
3x-2y-4x-y=
-x-3y

b) (a+3) - (3a-b+1)=
a+3-3a+b-1=
-2a+b+2

c) (-2) (x+2y-4)=
-2x-4y+8

d) 2(x+3y)-4(x-2)+(y-3)=
2x+6y-4x+8+y-3=
-2x+7y+5
1 1 1
2010-02-24T17:12:18+01:00
A)3x-2y-4x-y=-x-3y
b)a+3-3a+b+1=2a+b+2
C)-2x-4y+8
d)2x+6y-4x+8+y-3=-2x+7y+5
2010-02-24T17:14:44+01:00
A) (3x-2y) + (-4x-y)=3x-2y-4x-y=-x-3y
b) (a+3) - (3a-b+1)=a+3-3a+b-1=a-3a+b+3-1=-2a+b+2
c) (-2) (x+2y-4)=-2x-4y+8
d) 2(x+3y)-4(x-2)+(y-3)= 2x+6y-4x+8+y-3=2x-4x+6y+y+8==2x+7y+8